In-Vitro Investigation On Efficacy Of Selected Medicinal Plant Extracts On Rice Blast Fungus Magnaporthe Grisea - Madushika, U.B.; Nirosha, A.; Pakeerathan, K.; Mikunthan, G. (Faculty of Agriculture, Eastern University, Sri Lanka, 2022)
Being ranked next to wheat, Rice (Oryzae sativa L.), an important staple food of Sri Lanka, is globally hampered by blast disease caused by Magnaporthe grisea. Synthetic fungicides synthetic chemicals, an alternate method of using untapped indigenous resources wase xplored. An in-vitro investigation was carried out to test the efficacy of selected medicinal plant leaf extracts against M. grisea. 20% of Vernonia cinerea, Mentha arvensis, Aegle marmelos, Mimosa pudica and Ocimum tenuiflorum hot water leaf extracts were mixed with PDA media and tested for antifungal activities. Three replicates were maintained along with the non-plant extract as control. For the phytotoxic confirmation test was done on 100 paddy seeds treated with leaf extracts (20%). Experiments were arranged in a Complete Randomized Design. The mycelial growth of M. grisea and rice seed germination were recorded. The data were subjected to ANOVA and Tukey's HSD multiple comparison test to determine the best treatment at P <0.05 using SAS 9.1. Significant growth inhibition of 98.07% and no conidial production were observed only in O. tenuiflorum treatment whereas in other treatments inhibition percentages were less than 40.27% and were not significant among them at P < 0.05. The seed germination varied from 80 - 93% and indicated no phytotoxic activity of botanicals in seed germination. Therefore, the findings conclude that20% leaf extract of O. tenuiflorum could be useful to manage the blast fungi in paddy seed germination and extended field trials are needed for a recommendation.
Keywords: Rice blast; Ocimum tenuiflorum; Inhibition; Organic rice production; Oryza sativa